Routine Immunization of Adults in Canada: Review of the Epidemiology of Vaccine-Preventable Diseases and Current Recommendations for Primary Prevention - Michael D Parkins; Shelly A McNeil; Kevin B Laupland (Canadian Journal of Infectious Diseases and Medical Microbiology)
Vaccination is one of the greatest achievements in public health of the 20th century. However, the success of vaccine uptake and adherence to immunization guidelines seen in pediatric populations has not been observed among adult Canadians. As a result of the disparity in susceptibility to vaccine-preventable disease, there has been an increasing shift of vaccine-preventable childhood diseases into adult populations. Accordingly, morbidity and mortality due to vaccine-preventable illnesses now occur disproportionately in adults. All Canadians, irrespective of age, should have immunity to measles, mumps, rubella, tetanus, diphtheria, pertussis and varicella. All adult Canadians with significant medical comorbidities or those older than 65 years of age should receive the pneumococcal polysaccharide vaccine and yearly trivalent inactivate influenza vaccines. The present review summarizes the burden of illness of these vaccine-preventable diseases in the Canadian adult population and reviews the current immunization recommendations. Vaccination of all Canadians to these common agents remains a vital tool to decrease individual morbidity and mortality and reduce the overall burden of preventable disease in Canada.